Congenital ovary-intestinal adherence in a bitch - Silva, Carlos; Araújo, Bruno Marcel da Silva; Reis Filho, Carlos Henrique Ribeiro dos; Araujo, Endrigo Adonis Braga de; Silva, Renata Maria Monção da (Pubvet, 2019)
Congenital adhesions are present since birth as an embryological anomaly in the development of the peritoneal cavity. The present study aimed to report the case of congenital adherence of a Yorkshire bitch of 9 months submitted to elective ovariosalpingohysterectomy (OSH). In the anamnesis, the owner reported that the animal had never undergone any surgical procedure and its physiological state was within normal range. In the clinical examination, no changes in the parameters (heart rate, respiratory rate, temperature, capillary filling time, body score, lymph nodes, abdominal palpation and cardiopulmonary auscultation) were observed in the animal, as well as in the laboratory tests (Hemogram, ALT, FA, urea and creatinine). Thus, the animal was referred and subsequently submitted to the surgical procedure, during the exploratory laparotomy was identified the ovary-intestinal adhesion. Surgical correction (adhesiolysis) was performed, without complication during the procedure.
Keywords: adhesions; congenital; veterinary